Physicochemical and bioactive constituents, microbial counts, and color components of spray-dried Syzygium cumini L. pulp powder stored in different packaging materials under two controlled environmental conditions - Kumar, Vishal; Singh, Chandra Shekhar; Bakshi, Shiva; Kumar, Sudhir; Yadav, Satya Prakash; Al-Zamani, Zakarya Ali Saleh; Kumar, Pankaj; Singh, Upendra; Meena, Kamlesh Kumar; Bunkar, Durga Shankar; Paswan, Vinod Kumar (Frontiers in Nutrition, 2023)
Currently, the demand for functional food items that impart health benefits has been rising. Blackberry (Syzygium cumini L.) fruit has high anthocyanin content and other functional attributes. However, this seasonal fruit is highly perishable, and a large proportion of it goes unharvested and wasted worldwide. Spray drying of the fruit pulp can impart improved shelf life, ensuring long-term availability for consumers to exploit its health benefits. The storage quality varies according to the type of packaging material and the storage environment. Therefore, in this study, the shelf life span of the spray-dried Syzygium cumini L. pulp powder (SSCPP) was investigated during 6 months of storage under three types of packaging materials (i.e., polystyrene, metalized polyester, and 4-ply laminates) in a low-temperature environmental (LTE) and at ambient environmental conditions. The physicochemical stability of bioactive principles (TPC and TAC), microbial counts, and color components were analyzed at 0, 2, 4, and 6 months of storage. There was a significant gradual loss of dispersibility and solubility with an increase in flowability, bulk density, and wettability during the entire storage period for all three packaging materials. The TSS, pH, TPC, TAC, and microbial counts decreased in the SSCPP both at ambient and LTE conditions during the study. Among all the packaging materials, the 4-ply laminate was found to be the most appropriate and safe for storage of spray-dried SCPP at LTE conditions.